Respostas

  • Usuário do Brainly
2013-06-28T01:24:04-03:00

Observe que:

 

\text{x}=\dfrac{-\text{b}\pm\sqrt{\text{b}^2-4\cdot\text{a}\cdot\text{c}}}{2\cdot\text{a}}

 

Na equação -2\text{x}^2+9\text{x}+18=0, temos, \text{a}=-2, \text{b}=9 e \text{c}=18, logo:

 

\text{x}=\dfrac{-9\pm\sqrt{9^2-4\cdot(-2)\cdot18}}{2\cdot(-2)}}=\dfrac{-9\pm15}{-4}

 

Logo, as raízes são:

 

\text{x}'=\dfrac{-9+15}{-4}=\dfrac{-6}{-4}=\dfrac{3}{2}

 

\text{x}"=\dfrac{-9-15}{-4}=\dfrac{-24}{-4}=6

 

\text{S}=\{\frac{3}{2},6\}